1999
DOI: 10.1590/s0100-204x1999000800021
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da premunização da abóbora 'Menina Brasileira' com estirpes fracas do vírus-do-mosaico-do-mamoeiro - estirpe melancia

Abstract: RESUMO -Neste trabalho avaliou-se o efeito da premunização com duas estirpes fracas do vírus-domosaico-do-mamoeiro -estirpe melancia (papaya ringspot virus -type W, PRSV-W), combinada com a tolerância das plantas, no controle do mosaico e na produtividade da abóbora Menina Brasileira. Testes realizados em casa de vegetação mostraram que as plantas dessa cultivar premunizadas com as estirpes fracas PRSV-W-1 e 2 ficaram totalmente protegidas contra a infecção por uma estirpe severa de Campinas. Em condições de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
13

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
0
6
0
13
Order By: Relevance
“…The use of preimmunized plants with mild strains of this virus, which do not affect yield and development and protect them against the effects of severe isolates in the field, has been investigated for over ten years in Brazil. Rezende et al (1994), Rezende & Pacheco (1998), Rezende et al (1999), Dias & Rezende (2000), and Rabelo & Rezende (2004) showed that preimmunization was experimentally effective to control this virus disease in different species of cucurbits, with significant gains in production. Despite the promising results of this technique to control the common mosaic, there are no reports on the mechanism(s) that govern the protection provided by mild PRSV-W strains.…”
Section: Introductionmentioning
confidence: 99%
“…The use of preimmunized plants with mild strains of this virus, which do not affect yield and development and protect them against the effects of severe isolates in the field, has been investigated for over ten years in Brazil. Rezende et al (1994), Rezende & Pacheco (1998), Rezende et al (1999), Dias & Rezende (2000), and Rabelo & Rezende (2004) showed that preimmunization was experimentally effective to control this virus disease in different species of cucurbits, with significant gains in production. Despite the promising results of this technique to control the common mosaic, there are no reports on the mechanism(s) that govern the protection provided by mild PRSV-W strains.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, this technology has been utilized quite successfully for over three decades, for the control of citrus tristeza (Citrus tristeza virus -CTV) (Müller & Costa, 1968;Müller & Carvalho, 2001). It has also been proved to be efficient for control of mosaic caused by the Papaya ringspot virus -type W (PRSV-W) in some cucurbit species Rezende & Pacheco, 1998;Rezende et al, 1999;Dias & Rezende, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…ex Lam x C. moschata Duch.) plants showed that pre-immunization was efficient in controlling mosaic under greenhouse and field conditions (Dias & Rezende, 2000;Rezende & Pacheco, 1998;Rezende et al, 1999). This technology is already in use, at a small scale, to control this virus disease in commercial plantings, allowing significant yield gain.…”
Section: Introductionmentioning
confidence: 99%